Answer:
nike its observational
Step-by-step explanation:
Take any 2 points the answer will be the same.
For point 2 and 3 : (-4)-(2)/(0)-(-1) = -6
the answer is -6
So, since there are two equations, we can substitute one of them into the other. In this case, it would be easiest to substitute 2b=6a-14 into the other equations. But first, simplify by dividing both sides by 2. You bet b=3a-1
We can now plug this into the other equation
Sine the equation b=3a-1 results in the value of b, we have to plug in for the value of b in the other equation
So this is what we get after plugging in:
3a-(3a-1)=7
Now, simplify. 3a-3a+1=7
Since 3a-3a = 0, this equation results in a no solution
Answer:
The result is a no-solution, or Ф
Hope this helped!! :D
Answer:
Today: Tuesday, 12th January 2021
16.31 PM





Answer:
your answer is $15.45 because all you have to do is subtract 7.00 from 68.75 and then divide by 4